Simultaneous correction of functional posterior cross bite and midline shift - R Arvinth; Shailendra Singh Rana; Ritu Duggal; Om Prakash Kharbanda (Wolters Kluwer Medknow Publications, 2016)
The most frequent cause of functional posterior crossbite is the reduction in width of the maxillary dental arch. This posterior crossbite is associated with anterior crowding which is presented as an infrapositioned canine or a palatally positioned lateral incisor on one side; this leads to an upper midline shift toward the crowded side. The present case report shows the management of posterior crossbite with functional shift and upper midline shift simultaneously without adverse side effects. In this case, rapid maxillary expansion along with fixed appliance is used to correct posterior crossbite with the upper dental midline shift using reciprocal action of elastic transseptal ﬁbers.